Effects of biochar and Arbuscular mycorrhizae on bioavailability of potentially toxic elements in an aged contaminated soil. (November 2015) - Qiao, Yuhui; Crowley, David; Wang, Kun; Zhang, Huiqi; Li, Huafen
Abstract: Biochar pyrolyzed from corn stalks at 300 °C/500 °C and arbuscular mycorrhizae (AMF) were examined independently and in combination as possible treatments for soil remediation contaminated with Cd, Cr, Ni, Cu, Pb, Zn after 35 years following land application of sewage sludge in the 1970s. The results showed that biochar significantly decreased the heavy metal concentrations and their bioavailability for plants, and both biochars had similar such effects. AMF inoculation of corn plants had little effect on heavy metal bioavailability in either control or biochar amended soil, and no interaction between biochar and AMF was observed. Changes in DTPA extractable metals following biochar addition to soil were correlated with metal uptake by plants, whereas pore water metal concentrations were not predictive indicators. This research demonstrates positive benefits from biochar application for contaminated soil remediation, but remain ambiguous with regard to the benefits of simultaneous AMF inoculation on reduction of heavy metal bioavailability. Highlights: Biochar pyrolyzed from corn stalks at 300 °C/500 °C can increase the biomass of corn growing in a heavily contaminated soil. Biochar could significantly decrease bioavailability of heavy metals (Cd, Cr, Ni, Cu, Zn) for plants. Effects were not augmented by the addition of AMF although the production of glomalin is promoted by biochars. AMF had not reduced bioavailability of PTEs, no significant interaction between biochar and AMF inoculation was observed. Abstract : Biochar could significantly decrease bioavailability of heavy metals (Cd, Cr, Ni, Cu, Zn) for plants, but AMF had little such effects, biochar and AMF interaction is not valid.